N′-[1-(2-Hydroxyphenyl)ethylidene]-2-nitrobenzohydrazide methanol solvate - Xiao, Ge-Jiang (International Union of Crystallography, 2009)
In the title compound, C(15)H(13)N(3)O(4)·CH(3)OH, the dihedral angle between the two substituted benzene rings is 66.7 (2)°. An intramolecular O—H⋯N hydrogen bond is observed in the Schiff base molecule. In the crystal structure, the Schiff base and solvent molecules are linked into chains running along the a axis by intermolecular O—H⋯O and N—H⋯O hydrogen bonds.